Application Design of Company Asset Management Information System Case Study: STIKOM Surabaya - Susilo, Franstia Wira Sukma; Sukmaaji, Anjik; Widodo, Arifin Puji (Jurnal JSIKA, 2012)
As one of the Asset Management Department that works to serve the departments in STIKOM Surabaya in the use of assets, the inventarisation department is often deal with various operational problems. The problem that often occurs, is the problem the lack of information collection about the detail, location, lists of assets and economic life of electronic goods that are needed to perform the operations of the company. The absence of management on asset that have been removed, is also one the most common problem. In addition, depreciation of assets which are useful for removal and replacement assets planning, cannot be known. In the absence of an information system, management of the asset is still manual and not informative. Based on the above problems, then there will be ​​an asset management information system made by researcher that can provide detailed information and economic life of an asset to be discharged, and can take over management of the assets that have been removed. In addition, this system can provide information about the needs of electric power and information depreciation of assets owned. Calculation method is used declining balance method. In its application, the inventarisation department will be asked to fill in cost, the percentage of depreciation, useful lives and residual values ​​of assets. With a system that will be built, the inventarisation department can perform data collection on assets with more informative and can find out information on the depreciation of the cost of depreciation and net book value and know the needs of electric power assets. The inventarisation department can also handle operational issues properly and quickly. Keywords: assets, fixed assets, asset management, asset management information system.